Prolonged Hypercalcemia-Induced Psychosis - Lauren Nagy; Pratheek Mangini; Caitlin Schroen; Rehan Aziz; Anthony Tobia (Case Reports in Psychiatry)
Hypercalcemia is known to cause neuropsychiatric dysfunction including mood and cognitive changes and rarely, acute psychosis. High calcium levels can be a catalyst for neuronal demise, possibly due to glutaminergic excitotoxicity and dopaminergic and serotonergic dysfunction. While restoration of normal calcium levels or removal of a parathyroid adenoma has been shown to rapidly resolve neuropsychiatric symptoms, there have been rare reported cases of primary hyperparathyroid-related hypercalcemia with persistent symptoms of psychosis. In this case report, we will describe a patient with no past psychiatric history presenting with a protracted course of delirium and psychosis after a removal of a parathyroid adenoma which had caused prolonged exposure to hypercalcemia. The patient’s psychosis was unresponsive to psychotropic medication and required inpatient psychiatric care after medical clearance. Per medical records, before the patient was ultimately lost to follow-up, she continued to suffer from psychotic symptoms for at least 8 months. We will discuss the patient’s unusual hospital course and management and offer suggestions for future study.